Attitudes towards immigrants : a function of national in-group conception and perceived intergroup similarity. - Chew, Bing Rui. (2013)
Drawing on predictions of the black sheep effect, how perceived intergroup similarities might moderate the effects of national in-group conceptions on attitudes towards immigrants is explored in this study. The author also examines the role national in-group conception plays on attitudes towards immigrants. In addition, the author investigates whether similarity-attraction hypothesis or social identity theory is a better predictor for attitudes towards immigrants. 60 Singaporean Chinese participants were randomly assigned to either a civic or ethnic condition. Participants read an article that primed either a civic or ethnic national in-group conception, and completed a computerized questionnaire, which included a measure of perceived intergroup similarities and a list of dependent measures on attitudes towards immigrants from China. Consistent to the literature, some support was found for the main effect of national in-group conception on attitudes towards immigrants. The results from this study supported the similarity-attraction hypothesis over the social identity theory. However, the proposed interaction effect was not found on all dependent measures. The theoretical and practical implications, as well as the limitations of this study were addressed in the discussion section and future research directions were proposed.